Craig Owens portrait of a young critic - Blumenthal, Lyn 1949-1988; Horsfield, Kate ca. 20. Jh (Badlands Unlimited, 2018)
"The interview published in this book, Craig Owens: portrait of a young critic, originated in a video interview titled, 'Craig Owens: an interview,' which was recorded in New York City in 1984 and edited and finished in 1985. Lyn Blumenthal is interviewing Craig Owens...This collection of video interviews that Lyn and I made formed the basis of the On art and artists collection in the Video Data Bank at the School of the Art Institute of Chicago"--Preface
Includes contribution by Lynne Tillman
Keywords: Owens, Craig -- 1950-1990; Geschichte 1984-1985; Kunstkritik; Owens, Craig / Interviews; Owens, Craig; Art criticism; Interviews; Interview